Design and identification of a novel, functionally subtype selective GABA A positive allosteric modulator (PF-06372865) - Owen, Robert M.; Blakemore, David C; Cao, Lishuang; Flanagan, Neil; Fish, Rebecca; Gibson, Karl R; Gurrell, Rachel; Huh, Chan Woo; Kammonen, Juha; Mortimer-Cassen, Elisabeth; Nickolls, Sarah; Omoto, Kiyoyuki; et al. (Journal of medicinal chemistry, 2019)
The design, optimization, and evaluation of a series of novel imidazopyridazine-based subtype-selective positive allosteric modulators (PAMs) for the GABA(A) ligand-gated ion channel are described. From a set of initial hits multiple subseries were designed and evaluated based on binding affinity and functional activity. As designing in the desired level of functional selectivity proved difficult, a probability-based assessment was performed to focus the project's efforts on a single subseries that had the greatest odds of delivering the target profile. These efforts ultimately led to the identification of two precandidates from this subseries, which were advanced to preclinical safety studies and subsequently to the identification of the clinical candidate PF-06372865.